2022
DOI: 10.1111/jace.18475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative spectroscopic investigation of Dy3+ ions in different sesquioxide solid solution ceramics

Abstract: A comparative study of the spectroscopic properties of LuScO3:Dy, LuYO3:Dy, and YScO3:Dy was conducted to evaluate their application prospects in yellow laser generation. The absorption cross sections of Dy‐doped LuScO3, LuYO3, and YScO3 at 446 nm were calculated to be 0.67, 1.51, and 1.05 × 10−21 cm2, respectively. The Judd–Ofelt (J–O) theory was used to determine the J–O parameters as well as the spontaneous transition probability and fluorescence branching ratios. The fluorescence spectra of LuScO3:Dy, LuYO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Moreover, Dy 3+ possesses favorable absorption band around 450 nm, indicating that the yellow uorescence can be directly obtained using blue LD pumping. And this has been implemented in many materials, such as transparent ceramics, glasses and single crystals [7][8][9][10][11] . However, large number of studies have shown that the transition of Dy 3+ from 6 H 15/2 to 4 I 15/2 is a spin forbidden process, resulting in relatively weak blue absorption and yellow emission cross-sections of Dy 3+ , which greatly limits the development of Dy 3+ yellow lasers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dy 3+ possesses favorable absorption band around 450 nm, indicating that the yellow uorescence can be directly obtained using blue LD pumping. And this has been implemented in many materials, such as transparent ceramics, glasses and single crystals [7][8][9][10][11] . However, large number of studies have shown that the transition of Dy 3+ from 6 H 15/2 to 4 I 15/2 is a spin forbidden process, resulting in relatively weak blue absorption and yellow emission cross-sections of Dy 3+ , which greatly limits the development of Dy 3+ yellow lasers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been considerable interest in achieving yellow lasers in a single step through the commercial blue LD pumping technique. 8,13 Among the rare earth (RE) ions investigated for this purpose, Dy 3+ has shown the most promise. [14][15][16][17] When excited at 450 nm wavelength, Dy 3+ undergoes a transition from its ground state 6 H 15/2 to an excited state 4 I 15/2 , resulting in yellow emission through the 4 F 9/2 → 6 H 13/2 transition, as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%